Experimental Evaluation of a Mixed Controller That Amplifies Spatial Errors and Reduces Timing Errors - Marchal-Crespo, Laura; Baumann, Tanja; Imobersteg, Michael; Maassen, Steve; Riener, Robert (Frontiers in Robotics and AI, 2017)
Research on motor learning suggests that training with haptic guidance enhances learning of the timing components of motor tasks, whereas error amplification is better for learning the spatial components. We present a novel mixed guidance controller that combines haptic guidance and error amplification to simultaneously promote learning of the timing and spatial components of complex motor tasks. The controller is realized using a force field around the desired position. This force field has a stable manifold tangential to the trajectory that guides subjects in velocity related aspects. The force field has an unstable manifold perpendicular to the trajectory, which amplifies the perpendicular (spatial) error. We also designed a controller that applies randomly-varying, unpredictable disturbing forces to enhance the subjects’ active participation by pushing them away from their “comfort zone.” We conducted an experiment with thirty-two healthy subjects to evaluate the impact of four different training strategies on motor skill learning and self-reported motivation: i) No haptics, ii) mixed guidance, iii) perpendicular error amplification and tangential haptic guidance provided in sequential order, and iv) randomly-varying disturbing forces. Subjects trained two motor tasks using ARMin IV, a robotic exoskeleton for upper limb rehabilitation: Follow circles with an ellipsoidal speed profile, and move along a 3D line following a complex speed profile. Mixed guidance showed no detectable learning advantages over the other groups. Results suggest that the effectiveness of the training strategies depends on the subjects’ initial skill level. Mixed guidance seemed to benefit subjects who performed the circle task with smaller errors during baseline (i.e. initially more skilled subjects), while training with no haptics was more beneficial for subjects who created larger errors (i.e. less skilled subjects). Therefore, perhaps the high functional difficulty of the tasks limited the potential benefit of mixed guidance. Adding random disturbing forces during training reduced the learning effect size compared to no haptics. The unanticipated forces also decreased the subjects’ feelings of competence while did not increase their effort and interest. Further studies with mildly affected neurologically patients employing easier tasks need to be performed in order to evaluate the applicability of our approaches in rehabilitation.